Pemberdayaan Literasi Bahasa Melalui Media Pembelajaran berbasis Teknologi bagi Guru di Bandar Lampung - Widodo, Mulyanto; Samhati, Siti; Fernando Rizqi, Yoga; Fajar Aprian, Figo; Asmaul Husna, Siti (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The purpose of this community service is to empower teachers in Bandar Lampung City to analyze their needs in the use of learning technology. Provide training or solutions to utilize technology media to improve language literacy. Empower teachers to be more adaptive and innovative in language teaching by providing guidance and mentoring on character and literacy. In addition, teachers are also trained on how to create learning media with technology in empowering creative, digital-based language literacy. The design method used in this community service is classroom action through teachers. In collecting data, the community service team conducted observations at partner locations, interviewing teachers there about obstacles faced in teaching and learning. After that, the community service team carried out planning, implementation, and evaluation of activities. The results of the community service target achievement increased teachers' abilities in strengthening students' character and students' interest in reading. This can be seen from the evaluation of the implementation of language literacy empowerment through interesting technology-based learning media. In addition, students can also develop interest and appreciation for language and literature through enjoyable experiences.